FAKTOR YANG MEMPENGARUHI DIVIDEND POLICY PADA PERUSAHAAN MANUFAKTUR TAHUN 2018-2020 - Rahel Christiana Surya; Thio Lie Sha (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
This study aims to determine the effect of total asset turnover, firm growth, profitability, firm size on dividend policy in manufacturing companies in 2018-2020. The sample was selected based on the purposive sampling method and the valid data were 21 companies. The data processing technique in this study uses multiple regression analysis assisted by Eviews version 12 and Microsoft Excel 2010. The results of this study indicate that total asset turnover and profitability have a significant negative effect on dividend policy, while firm growth and firm size have no significant effect on dividend policy. The implication of this research is the importance of analyzing the prospects and performance of the company in order to improve dividend policy and attract investors to invest.